Association between treatment of superficial bladder cancer and 10‐year mortality in older adults with multiple chronic conditions. Issue 23 (5th October 2018) - Garg, Tullika; Young, Amanda J.; O'Keeffe‐Rosetti, Maureen; McMullen, Carmit K.; Nielsen, Matthew E.; Kirchner, H. Lester; Murphy, Terrence E.
Abstract : Background: Multiple chronic conditions (MCC) are common among older patients with cancer; however, the exclusion of these patients from clinical trials has resulted in scarce knowledge concerning outcomes, resulting in variations in treatment. Superficial bladder cancer (SBC) disproportionately affects older adults, yet to the authors' knowledge few studies to date have examined whether treatment improves long‐term survival. In the current study, the authors evaluated the association between treatment of SBC and 10‐year mortality in medically complex older adults. Methods: The authors identified 1800 older (aged ≥60 years) patients with SBC (American Joint Committee on Cancer stage ≤I) from 2 community‐based health systems who received treatment (bladder instillation and/or transurethral resection) or observation. Cox proportional hazards regression was performed adjusting for age, sex, race, health system, stage of disease/grade, and MCC (≥2 baseline chronic conditions). Propensity score analysis using stabilized inverse probability of treatment weights was used to compare 10‐year mortality in the 2 treatment groups with adjustment for covariates. Results: Overall, 1485 patients (82.5%) and 315 patients (17.5%) received treatment and observation, respectively. In unweighted multivariable analysis, treatment was associated with a 30% reduction in death (adjusted hazard ratio [HR], 0.70; 95% confidence interval [95% CI], 0.58‐0.85 [ P <.01]) and MCC with a 72% increase in death (adjusted HR, 1.72; 95% CI, 1.44‐2.05 [ P <.01]). Weighted analysis with adjustment (doubly robust) also demonstrated a survival benefit for treatment (adjusted HR, 0.66; 95% CI, 0.52‐0.84 [ P <.01]). Conclusions: The results of the current study demonstrated a clinically meaningful association between cancer treatment and survival benefit in older, medically complex patients with SBC, even after adjustment for medical complexity. These data provide a foundation for future work aimed at personalizing the treatment guidance of older patients with cancer with MCC. Abstract : In this retrospective study from 2 community‐based health systems, the authors report that older adults with superficial bladder cancer experience a long‐term survival benefit from cancer treatment even after adjustment for multiple chronic conditions. These data provide a foundation for patient‐centered decision making in medically complex older adults with superficial bladder cancer.